1981
DOI: 10.1002/1097-0142(19810315)47:6<1267::aid-cncr2820470607>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Leg function after radiotherapy for Ewing's sarcoma

Abstract: Twenty-nine patients with Ewing's sarcoma of the lower extremity who survived for two or more years following therapy (5000 rad locally and systemic chemotherapy) were studied to assess functional status of the affected leg. Twenty-two of twenty-nine were alive and were reexamined; the deceased patients were evaluated by record review. Twenty-two of the twenty-nine had serial radiographs, which were reviewed to assess growth change induced by radiation. The living patients were divided on the basis of clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…These changes may affect muscle cell function and consequently affect muscle contraction force [7,8]. During radiation therapy NPC patients often use a nasogastric tube for feeding to relieve the pain of mucosal ulcers, and the presence of that tube may decrease the backward tongue movement.…”
supporting
confidence: 49%
“…These changes may affect muscle cell function and consequently affect muscle contraction force [7,8]. During radiation therapy NPC patients often use a nasogastric tube for feeding to relieve the pain of mucosal ulcers, and the presence of that tube may decrease the backward tongue movement.…”
supporting
confidence: 49%
“…In our series the functional results were the same in patients treated with local resection compared to those treated with radiotherapy alone, emphasising that deficits such as fibrosis and leg length discrepancy can be considerable after radiotherapy [8,10]. Major complications such as infection, skin necrosis or nerve palsies are seen after pelvic resections.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, certain factors, such as large size [8,9] and pelvic lesions [2, 5, 6, 14, 15, 17, 181, …”
Section: Introductionmentioning
confidence: 99%
“…irradiated bone 9 months to 22.2 years after RT. This is consistent with the findings of Jentzsch et al, who found a 44% incidence of fractures in the irradiated femur of Ewing's sarcoma patients (4). Fractures may be secondary to a large biopsy site and impaired healing by RT (12).…”
Section: Vincristine Doxorubicin and Cyclophosphamidementioning
confidence: 99%